Ankle structure and neuromuscular characteristics in individuals with chronic ankle instability - ÖZGÜL, BAHAR (Taylor and Francis Ltd., 2019)
[No abstract available]
Keywords: ankle sprain; chronic ankle instability; muscle activity; stability; ultrasound